Teens and Sexual Harassment: Making a Difference - Kate Fogarty (EDIS)
One of the unfortunate offshoots of our culture’s obsession with sex is problems with sexual harassment. Sexual harassment harms the sexual integrity of teens in their peer relationships. This revised 7-page fact sheet describes sexual harassment at school, workplace, and online, its effect on teens, and tips for educators, volunteers, parents, and youth. Written by Kate Fogarty and published by the UF Department of Family Youth and Community Sciences, March 2011.